From persistence to progress: assessing per- and polyfluoroalkyl substances (PFAS) environmental impact and advances in photo-assisted fenton chemistry for remediation - Walker, Tasia; Milligan, Kimberly A. (Frontiers in Environmental Chemistry, 2025)
Per- and polyfluoroalkyl substances (PFAS) are highly stable anthropogenic compounds characterized by their persistence in the environment and potential for bioaccumulation. This review investigates the physicochemical properties that underlie their environmental persistence, particularly the robustness of the carbon-fluorine bond. It also examines the synthesis processes of PFAS, their extensive applications across various industries, and the related health risks, including endocrine disruption and carcinogenic effects. The occurrence of PFAS in diverse environmental matrices, such as soil, water, and biota, is analyzed. Additionally, this study assesses advanced oxidation processes (AOPs), with an emphasis on Fenton-based treatments for the oxidative degradation of PFAS. Methods such as Photo-Assisted Anodic Fenton Treatment (P-AAFT) are highlighted for their promise in achieving complete mineralization of PFAS. The findings highlight the critical need for continued research and policy advancement to address the environmental and health challenges posed by PFAS, underscoring the urgent requirement for effective remediation strategies to mitigate PFAS contamination.